Transcending Cultures Through Humor: A Study of Wit and Satire in The Works of Stephen Leacock, Mark Twain, And R.K. Narayan - Banazeer Banu, G.; Gunasekaran, S. (Journal of Neonatal Surgery, 2025)
Humor serves as a universal language that transcends cultural and temporal boundaries. This paper explores the wit, satire, and narrative brilliance in the works of Stephen Leacock, Mark Twain, and R.K. Narayan, focusing on their distinctive approaches to humor in storytelling. By examining select works, the study aims to highlight the cultural contexts, linguistic subtleties, and thematic depth that define their humor. The objectives of the research are to identify the techniques employed by these authors to evoke laughter, analyze how humor reflects the socio-political and cultural realities of their respective times, and examine its role in shaping narrative engagement and reader empathy. The research employs a comparative literary method, analyzing primary texts and employing tools from humor theory, narratology, and cultural studies. It juxtaposes the situational comedy of Leacock, the biting satire of Twain, and the understated humor of Narayan to uncover shared themes and distinct narrative strategies. Close reading and textual analysis form the core of the methodology, supported by secondary research to contextualize the findings. The study reveals that while Leacock's humor often hinges on absurdity and hyperbole, Twain uses satire as a critique of societal hypocrisies, and Narayan employs gentle irony to depict the idiosyncrasies of Indian life. Together, their works illustrate how humor serves as both entertainment and a lens for social commentary. The findings have significant implications for humor studies and cross-cultural literary analysis, offering insights into the ways humor bridges diverse cultural landscapes and enhances narrative impact. The research contributes to understanding humor as a vital literary device with profound societal relevance.